GREEN BEAUTY IN DIGITAL ERA : THE ROLE OF INFLUENCER CREDIBILITY AND HOMOPHILY, MEDIATED BY MIMICRY DESIRE, ON BRAND TRUST IN GREEN BEAUTY PRODUCTS - Zahra Pandya; Iqbal Daulay, M. Yasser (JURNAL MANAJEMEN MOTIVASI, 2026)
The purpose of this study is to investigate how brand trust for green beauty goods is shaped by homophily and influencer credibility, with mimicry desire serving as a mediator. This study uses a purposive sampling technique with 130 respondents who use eco-friendly beauty products in addition to a quantitative approach using SEM-PLS analysis with SmartPLS 4 software. A questionnaire was used to gather the data. According to the study's findings, brand trust and mimicry desire are significantly positively impacted by influencer credibility and homophily.